Fatty acid composition of Spirulina sp., Chlorella sp. and Chaetoceros sp. microalgae and introduction as potential new sources to extinct omega 3 and omega 6 - Homan Gorjzdadeh (Iranian South Medical Journal, 2016)
Background: This study was carried out to determine the oil fatty acids from two special species of microalgae; Spirulina sp.,Chlorella sp. and also Chaetoceros sp. collected from Bahmanshir River.